Comparative Study of Different Antibiotic Regimens in Managing Paediatric Dental Infections (Bangladesh Journal of Medical Science, 2025)
Background Pediatric dental infections, particularly those of odontogenic origin, are a common concern in dental practice. “Antibiotic therapy plays a crucial role in managing these infections, especially when accompanied by systemic signs of infection such as fever or facial swelling. This study aims to compare the efficacy of different antibiotic regimens in managing pediatric dental infections. Materials and Methods A total of 200 pediatric patients aged between 3 to 12 years presenting with dental infections were included in this comparative study. Patients were randomly assigned to one of three treatment groups. Group A received amoxicillin-clavulanate (500 mg/125 mg, twice daily), Group B received clindamycin (300 mg, three times daily), and Group C received azithromycin (500 mg once daily). All patients were monitored for resolution of infection symptoms such as pain, swelling, and fever over a 7-day period. Clinical improvement was assessed using a standardized infection control score (ICS) based on these symptoms at baseline and on days 3, 5, and 7. Results Out of 200 patients, 65 (32.5%) were in Group A, 70 (35%) in Group B, and 65 (32.5%) in Group C. By day 7, clinical resolution of infection (ICS ≤ 1) was achieved in 90% of patients in Group A, 85% in Group B, and 75% in Group C. Group A showed the fastest reduction in symptoms with significant improvement observed by day 3 (p < 0.05). Group C demonstrated the slowest response, with fewer patients showing complete resolution by day 7 (p = 0.07 compared to Group A). Mild side effects, including gastrointestinal upset, were reported in 10% of Group A, 5% of Group B, and 15% of Group C. Conclusion Amoxicillin-clavulanate (Group A) demonstrated superior efficacy in managing pediatric dental infections compared to clindamycin and azithromycin, with faster symptom resolution and a higher rate of clinical improvement. Clindamycin may serve as an effective alternative in cases of penicillin allergy”, while azithromycin exhibited the slowest response but was welltolerated. Further research is needed to refine antibiotic selection based on patient-specific factors such as age and allergy status.BJMS, Volume: 24. Supplementary Issue 2025, Page : 99-103